Utilization of Mind Mapping Media to Improve Student's Social Intelligence In Integrated Social Studies Learning at Junior High School 1 Lumar Bengkayaang Regency - Warneri Warneri (STKIP Singkawang, 2023)
The learning process for Integrated Social Studies subjects at the Junior High School level still requires innovation in the development and the use of learning media in delivering the ideas. The purpose of this study was to determine the activities of teachers and students in the learning process using Mind Mapping learning media. This research used action research method with 3 cycles. Description of students' social intelligence after the learning process for Integrated Social Studies subjects using Mind Mapping for each action that goes well according to plan. Teacher and student activities during the implementation of the action can run well, the results of observations show an increase, namely the score in the first cycle of action is 54, and in the second cycle of action is 60, there is an increase of 11.11% and in the third cycle of action it is 64, an increase of 6.67% compared to the implementation of the action cycle 2. This means that there is a significant increase in the activities of teachers and students when implementing the Integrated Social Studies learning process using Mind Mapping media at Junior High School1 Lumar, Bengkayang Regency.